Mikromycety, mykotoxiny a zdraví clovĕka - Ostrý, V (Casopis lekaru ceskych, 1999)
Mycotoxins are toxic metabolites produced by certain toxigenic microscopic fungi (moulds) in and on foods. Consequently mycotoxin-containing foods have been found all over the world: Africa, Asia, North and South America, Australia and Europe. The extent of the problem is greater in some parts of the world than in others because their climatic conditions are more favourable for mould growth and thus synthesis of mycotoxins. These toxins have been associated with various diseases-mycotoxicoses in humans throughout the world (ergotism, alimentary toxic aleukia, aflatoxicosis, balkan nephropathy, yellow rice disease, oesophageal cancer etc.). Mycotoxins can enter the food chain by one of two major routes: direct contamination resulting from the use of a food components contaminated with mycotoxins and indirect contamination resulting from the growth of toxigenic fungi of the food. Investigations of mycotoxins in foodstuffs, in human urine and human milk were incorporated into the system of Environmental Health Monitoring in the Czech Republic. The risk of acute toxic effects of mycotoxins was usually considered to be minimal in the Czech Republic. The risk of later toxic effects (particularly carcinogenic risk) after very low single or repeated mycotoxin concentrations in foodstuffs is very important.
Keywords: Food Microbiology; Mycotoxins; Fungi; potravinářská mikrobiologie; lidé; kontaminace potravin; Foodborne Diseases; nemoci přenášené potravou; houby; mykotoxiny; Food Contamination; Humans